Epidemiology and Treatment of Multidrug-Resistant and Extensively Drug-Resistant Pseudomonas aeruginosa Infections - Horcajada, Juan P; Montero, Milagro; Oliver, Antonio; Sorlí, Luisa; Luque, Sònia; Gómez-Zorrilla, Silvia; Benito, Natividad; Grau, Santiago (Clinical microbiology reviews, 2019)
In recent years, the worldwide spread of the so-called high-risk clones of multidrug-resistant or extensively drug-resistant (MDR/XDR) has become a public health threat. This article reviews their mechanisms of resistance, epidemiology, and clinical impact and current and upcoming therapeutic options. and treatment studies and pharmacokinetic and pharmacodynamic (PK/PD) models are discussed. Polymyxins are reviewed as an important therapeutic option, outlining dosage, pharmacokinetics and pharmacodynamics, and their clinical efficacy against MDR/XDR infections. Their narrow therapeutic window and potential for combination therapy are also discussed. Other "old" antimicrobials, such as certain β-lactams, aminoglycosides, and fosfomycin, are reviewed here. New antipseudomonals, as well as those in the pipeline, are also reviewed. Ceftolozane-tazobactam has clinical activity against a significant percentage of MDR/XDR strains, and its microbiological and clinical data, as well as recommendations for improving its use against these bacteria, are described, as are those for ceftazidime-avibactam, which has better activity against MDR/XDR , especially strains with certain specific mechanisms of resistance. A section is devoted to reviewing upcoming active drugs such as imipenem-relebactam, cefepime-zidebactam, cefiderocol, and murepavadin. Finally, other therapeutic strategies, such as use of vaccines, antibodies, bacteriocins, anti-quorum sensing, and bacteriophages, are described as future options.